Paradigma Psikologi Komunikasi dalam Memandang Permasalahan Melalui Nilai-nilai Stoikisme di Kalangan Remaja - Ekowati Sari (Prisani Cendekia Institute, 2023)
The essential psychological components have an impact on the psychological perception of communication and social interaction. Seeing the problem is sometimes based on experience and knowledge stored in the mind's memory which positions itself as the Actual Self, Ideal Self and Ought Self. Simple life advise, arguably most commonly heard in philosophy, including stoicism philosophy. Stoicism is a philosophy that encourages people to live realistically, foresee, and analyze themselves. Not imagining and must learn to anticipate the worst. Through stoicism, respecting time is a real process that must be studied and faced with sincerity in order to live a better life than before. Moreover, the probematics of adolescent life today is considered more complex due to the rapid development of the times and makes teenagers to be more careful in solving problems